Upaya Meningkatkan Kognitif Anak Melalui Metode Pemberian Tugas Media Mengerjakan Maze - Putu Adi Kristiani; Kadek Suartini; Luh Srinadi; Maria Yustina Nggera Ngaba (Early Childhood Education Development and Studies (ECEDS), 2021)
This study is underpinned by the salient issues apparent in the realm of children's cognitive development. The primary objective of this investigation is to ascertain the extent to which the cognitive advancement of children, specifically in problem-solving through Maze activities, can be augmented subsequent to the application of task assignment methodologies. The method used is data collection, using the assignment method while the data analysis method is descriptive analysis. The problem raised in this research is whether the application of the method of giving assignments through doing a maze (finding traces) can solve simple problems in the cognitive field in children. In this study, it produced data taken based on a survey of students at the State Kindergarten in Tukadmungga Village. With these data, it can be seen that the effectiveness of tracking activities to improve cognitive abilities in children aged 5 to 6 years is very effective.